Progressive phonagnosia in a telephone operator carrying a C9orf72 expansion. (November 2020) - Didic, Mira; Aglieri, Virginia; Tramoni-Nègre, Eve; Ronat, Lucas; Le Ber, Isabelle; Ceccaldi, Mathieu; Belin, Pascal; Felician, Olivier
Abstract: Selectivity is the rule, rather than the exception, in neurodegenerative disease. A retired telephone operator carrying a C9orf72 expansion developed phonagnosia, a selective impairment of voice recognition, contrasting with intact person knowledge and recognition of faces, as a presenting sign of genetically confirmed fronto-temporal dementia. Since the dysfunction in this patient fell into his area of professional expertise, we discuss if overload in voice related neural networks might have caused failure propagating to connected nodes. The interaction with downstream molecular events, triggered by the C9orf72 expansion, may have led to breakdown at the network level, leading to this specific phenotype.